DESIGN OF REMOTE CONTROLLED HEART MONITORING SYSTEM - Eşme, Engin; Ünsaçar, Faruk (LIFE: International Journal of Health and Life-Sciences, 2019)
The biological signal generated by the pulse is taken to the PC environment by means of an electrode, a preamplifier and a data acquisition (DAQ) card. An image is presented on the graphical display applying signal processing methods on the electrocardiogram (ECG) signals obtained on the PC. It has an easy-to-use interface supported by graphics on both the patient side and the specialist side. The ECG data is sent to the long-distance terminal via the GSM modem. The biggest advantage of using a GSM modem is to ensure that the specialist is independent of the place. Thus, the specialist can contact the patient at any time and at any place. The specialist analyzing ECG data can remotely manage the defibrillator device, if needed.